Separation of Pb(II) Ion with Tetraacetic Acid Derivative of Calix[4]arene by Using Droplet-based Microreactor System - Yehezkiel Steven Kurniawan; Mizuki Ryu; Ramachandra Rao Sathuluri; Wataru Iwasaki; Shintaro Morisada; Hidetaka Kawakita; Keisuke Ohto; Masatoshi Maeki; Masaya Miyazaki; Jumina Jumina (Indonesian Journal of Chemistry, 2019)
In this study, the microreactor system was investigated and compared with the batch-wise system as rapid and effective extractive Pb(II) separation over Fe(III), Cu(II) and Zn(II) with tetraacetic acid calix[4]arene. By using a microreactor system, the Pb(II) extraction percentages reached the maximum of 73, 89 and 100% in 8 sec residence time at equilibrium pH of 2.00, 2.25 and 2.50, respectively. The stripping percentage was 92% at 8 sec residence time by using a microreactor system with 2.0 M HNO3 as a stripping reagent. Complete separation of Pb(II) over Fe(III), Cu(II) and Zn(II) ions with the tetraacetic acid calix[4]arene in a competitive metal system was achieved at pH 2.00. However, the batch system required 24 h to reach the equilibrium for both extraction and stripping processes. The results suggested that the microreactor system enhanced the Pb(II) extraction and stripping rate up to 104 times faster than the batch-wise system.